2014
DOI: 10.3389/fnbeh.2014.00163
|View full text |Cite
|
Sign up to set email alerts
|

EEG-microstate dependent emergence of perceptual awareness

Abstract: We investigated whether the differences in perceptual awareness for stimuli at the threshold of awareness can arise from different global brain states before stimulus onset indexed by the EEG microstate. We used a metacontrast backward masking paradigm in which subjects had to discriminate between two weak stimuli and obtained measures of accuracy and awareness while their EEG was recorded from 256 channels. Comparing targets that were correctly identified with and without awareness allowed us to contrast diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 78 publications
3
57
0
Order By: Relevance
“…At each sample during the cue-target delay, the mean phase angles for predictive and unpredictive cues were compared using the Watson-Williams test, a circular analog of the t test, which tests the hypothesis that the two samples of angles have different phase distributions (23). This test takes into consideration the mean phase angle and the circular variance of the angles in each sample, and it has been widely used to assess phase differences in electrophysiological data (24)(25)(26)(27). We tested for phase differences separately for long and short delays across the entire period between cue and target onset.…”
Section: Significancementioning
confidence: 99%
“…At each sample during the cue-target delay, the mean phase angles for predictive and unpredictive cues were compared using the Watson-Williams test, a circular analog of the t test, which tests the hypothesis that the two samples of angles have different phase distributions (23). This test takes into consideration the mean phase angle and the circular variance of the angles in each sample, and it has been widely used to assess phase differences in electrophysiological data (24)(25)(26)(27). We tested for phase differences separately for long and short delays across the entire period between cue and target onset.…”
Section: Significancementioning
confidence: 99%
“…It has also been repeatedly demonstrated that the microstate at the moment of appearance of an external stimulus influences the processing of this stimulus in the brain (for review, see Britz and Michel, 2011). For example, it has been shown that commission errors in a stroop task are more frequent when the stimulus was presented during a specific microstate configuration (Britz and Michel, 2010), and perceptual awareness of two weak stimuli presented at the threshold of discrimination depends on pre-stimulus microstate (Britz et al, 2014). Spontaneous perceptual reversals of ambiguous visual stimuli such as the Necker cube or during binocular rivalry were shown to depend on the microstate topography at the moment of stimulus presentation (Britz et al, 2009, Britz et al, 2011, Pitts and Britz, 2011).…”
Section: Microstates As Indicators Of Resting-state Brain Activitymentioning
confidence: 99%
“…Differences in underlying generators are taken to indicate that different brain networks are activated, which in turn suggests the implication of different sets of cognitive processes. Microstate analyses have been applied to language production studies (B€ urki, Pellet-Cheneval, & Laganaro, 2015;Fargier & Laganaro, 2017;Laganaro, 2014) as well as in various other cognitive domains (e.g., Britz, Díaz Hern andez, Ro, & Michel, 2014;Murray, Camen, Gonzalez-Andino, Bovet, & Clarke, 2006).…”
Section: Microstate Analysismentioning
confidence: 99%